L'Islam dans l'Afrique nègre. La civilisation souahilie - Bouvat, L. (Revue du monde musulman, 1907)
Keywords: Zanzibar

Agreement Between the United Kingdom and France Respecting Commercial Relations Between France and Zanzibar. Signed at London, June 27, 1901 (1902)
Keywords: Zanzibar

Autobiographie des Arabers Schech Hamed bin Muhammed el Murjebi, genannt Tippu Tip - Brode, Heinrich (Mittheilungen des Seminars für Orientalische Sprachen an der königlichen Friedrich Wilhelms-Universität zu Berlin, 1902)
Keywords: Tippo Tip (1837-1905); Zanzibar

Der Mord Sejid Thueni's und seine Sühne. Eine Erzählung im Omandialekt - Brode, Heinrich (Mittheilungen des Seminars für Orientalische Sprachen an der königlichen Friedrich Wilhelms-Universität zu Berlin, 1902)
Keywords: Zanzibar

Tippoo Tib, the story of his career in Central Africa - Brode, Heinrich (Edward Arnold, 1907)
Keywords: Tippo Tip (1837-1905); Zanzibar

Tippu Tip: Lebensbild eines zentral-afrikanischen Despoten - Brode, Heinrich (Baensch, 1905)
Keywords: Tippo Tip (1837-1905); Zanzibar

Zanzibar in contemporary times; a short history of the southern East in the nineteenth century - Lyne, Robert Nunez (Hurst and Blackett, 1905)
Keywords: Zanzibar

Il diritto ereditario musulmano secondo la dottrina degli arabi ibāḍiti di Zanzibar e dell’Africa orientale - Guidi, Ignazio (Rivista Coloniale, 1906)
A translation of Sachau 1894 (his translation from Basyāwī’s al-Mukhtaṣar). Il diritto ereditario musulmano secondo la dottrina degli arabi ibāḍiti di Zanzibar e l’Africa Orientale. Rome: Istituto Coloniale Italiano, 1906, (59 pp.).
Keywords: Fiqh; Zanzibar

Il diritto ereditario musulmano secondo la dottrina degli arabi ibāḍiti di Zanzibar e dell’Africa orientale - Guidi, Ignazio (Rivista Coloniale, 1906)
A translation of Sachau 1894 (his translation from Basyāwī’s al-Mukhtaṣar). Il diritto ereditario musulmano secondo la dottrina degli arabi ibāḍiti di Zanzibar e l’Africa Orientale. Rome: Istituto Coloniale Italiano, 1906, (59 pp.).
Keywords: Fiqh; Zanzibar

Le droit abadhite chez les musulmans de Zanzibar et de l’Afrique orientale - Imbert, A. (Adolphe Jourdan, 1903)
An abstract of Sachau 1894, translation of the chapters on the law of succession (ch. 61-77) and testament (ch. 58) in Abū ‘l-Ḥasan ʿAlī b. Muḥ. b.ʿAlī al-Basyāwī’s Mukhtasar al-Basyawī (Zanzibar 1886) (pp. 9-12), and a comparison with chapter 21 of ʿAbd al-ʿAzīz b. Ibr. al-Thamīnī’s Kitāb al-Nīl, translated by Zeys 1895 (12-19). An abstract of Sachau 1898a (19-21).
Keywords: Fiqh; Zanzibar